2014
DOI: 10.1021/es504667r
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Oxides, Sulfur Trioxide, and Mercury Emissions during Oxy-fuel Fluidized Bed Combustion of Victorian Brown Coal

Abstract: This study investigates, for the first time, the NOx, N2O, SO3, and Hg emissions from combustion of a Victorian brown coal in a 10 kWth fluidized bed unit under oxy-fuel combustion conditions. Compared to air combustion, lower NOx emissions and higher N2O formation were observed in the oxy-fuel atmosphere. These NOx reduction and N2O formations were further enhanced with steam in the combustion environment. The NOx concentration level in the flue gas was within the permissible limit in coal-fired power plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…Furthermore, NOx emissions were found to increase with the increasing O 2 concentrations in feed gas, which is as a result of an increase in particle temperature, thus enhancing NOx conversion. On the contrary, N 2 O formation was found to be greater under oxy‐combustion conditions than in air combustion; nonetheless, it was observed to decrease with an increase in bed temperature . Experimental results also showed that the addition of steam and maintaining a fixed O 2 concentration in the furnace promotes further NOx reduction and increase N 2 O formation .…”
Section: Design and Operational Issuesmentioning
confidence: 91%
See 3 more Smart Citations
“…Furthermore, NOx emissions were found to increase with the increasing O 2 concentrations in feed gas, which is as a result of an increase in particle temperature, thus enhancing NOx conversion. On the contrary, N 2 O formation was found to be greater under oxy‐combustion conditions than in air combustion; nonetheless, it was observed to decrease with an increase in bed temperature . Experimental results also showed that the addition of steam and maintaining a fixed O 2 concentration in the furnace promotes further NOx reduction and increase N 2 O formation .…”
Section: Design and Operational Issuesmentioning
confidence: 91%
“…NOx emissions from CFB combustion have been found to be typically less than half those from bubbling beds with similar fuels and operating temperatures . Experimental results in FB boilers showed that NO emission in oxy‐combustion is lower than that under air‐firing atmosphere, because of the lower temperatures as well as higher char and CO concentrations in the dense bed, which was common for several literature sources . The lower amount of NOx formation in Oxy‐fuel FB combustion can also be attributed to the absence of nitrogen in the oxidant feed.…”
Section: Design and Operational Issuesmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, more N 2 O was emitted because the added KOH raised the pH of the sludge and various intermediate products, such as NH 2 OH and NO 2 À -N, were released into the volatile to form N 2 O [34]. However, N 2 O formation can be prevented by increasing the combustion temperature during the combustion [35]. The curves of NOx release as a function of the pyrolysis temperature were almost equivalent to those of NO as NO represented the major portion of NOx (Fig.…”
Section: Average Emission From Volatile Combustionmentioning
confidence: 99%